A Case of Acute Myopericarditis in a Patient with Human Metapneumovirus (hMPV) Respiratory Infection - Wang, Li (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.